Biodiversity of Northern Italy popcorn: a study on genetic diversity and agronomic performances of traditional landraces - Lezzi, Alessandra; Stagnati, Lorenzo; Petretto, Elena; Soffritti, Giovanna; Lodetti, Silvano; Rossi, Graziano; Lanubile, Alessandra; Marocco, Adriano; Busconi, Matteo (Frontiers in Plant Science, 2025)
Popcorn (Zea mays spp. mays - Everta) is an ancient and widely recognized maize type, of American origin, enjoyed for centuries worldwide and still highly valued for its unique popping trait. Italy, considered a secondary center of maize differentiation, still holds a rich diversity of local maize landraces survived on farm and also ex situ stored. Despite this genetic wealth, Italian popcorn varieties have largely been neglected in modern breeding programs and remain poorly characterized, with only fragmented and incomplete data available. Recent studies have confirmed the widespread presence of traditional popcorn landraces across Italy, also if relegate to small garden cultivations, yet a comprehensive understanding of their genetic and agronomic traits remains lacking. This underscores the urgent need to preserve and document these landraces to conserve biodiversity and protect Italy’s cultural heritage. In response to this gap, in this study, ten Italian popcorn landraces were collected and morphological characterization was performed. Moreover, a genetic characterization of 282 individuals was conducted using a GBS approach. The morphological characterization revealed significant phenotypic and agronomic variability for a total of 13 traits including susceptibility to fungal infection and popping traits, whereas the genetic one identified 313,342 SNP variants, uncovering evidence of local adaptation and provided insights into population structure by Admixture analysis, which revealed the presence of 8 ancestral populations consistently with morphological and historical data. This work sheds light on these neglected landraces, offering valuable information for biodiversity conservation and future breeding efforts, particularly in marginal areas where smallholder cultivation remains crucial.